Energy-Related Infrastructure Efficiency and Environmental Performance in ASEAN-5 - Laili Fitria; R. Putra Maha Muda (PT Penjaminan Infrastruktur Indonesia (Persero), 2026)
This paper examines how infrastructure efficiency, proxied by GDP per unit of energy use, relates to environmental and economic factors in ASEAN-5 countries. The study covers Indonesia, Malaysia, the Philippines, Thailand, and Vietnam from 2010 to 2023, using annual data from the World Bank’s World Development Indicators. The empirical analysis applies pooled ordinary least squares, fixed-effects, and random-effects panel models, with the Hausman specification test to determine the preferred estimator. The regression sample is based on available country-year observations after accounting for missing data. The fixed-effects results show that carbon dioxide emissions per capita are negatively and significantly associated with infrastructure efficiency, while electricity consumption per capita is positively and significantly associated with it. GDP per capita and the renewable energy share have positive coefficients in the fixed-effects model, but these estimates are not statistically significant at conventional levels. Overall, the findings suggest that lower CO₂ emissions per capita and higher electricity consumption per capita are more consistently associated with infrastructure efficiency, while GDP per capita and renewable energy share show less robust statistical relationships in the present sample. These results highlight the importance of combining cleaner energy use with more productive energy systems.